Induction of parturition with prostaglandin in Black Bengal goats - GIRI, S; SINGH, M P; SINHA, A K; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on twenty-four healthy pregnant Black Bengal goats. Parturition was induced successfully in advance stage of pregnancy using intramuscular injection of 0.15, 0.22 and 0.30 mg of Tiaprost, a PGF2a analogue on day 136. The parturition induction interval, time from onset of kidding to expulsion of fetus (es), time from delivery oflast fetus to expulsion of fetal membranes were shortest with 0.22 mg Tiaprost followed by 0.30 and 0.15 mg dose. There was no adverse effect of treatment on fetal membranes expulsion. It was concluded that parturition could be induced successfully by using different doses of PGF 2a analogue.